Biomembrane mimics and their roles in anti-bacterial drug discovery - Xiaohui Hu; Kin Tam (International Association of Physical Chemists (IAPC), 2017)
Cell membrane is at the frontline of the battle between pathogenic microbe and host. A thorough understanding of bacterial membrane is fundamental to tackle infection disease. Membrane mimetic provides a powerful tool for mechanistic interrogation of drug-membrane interaction. Herein, we summarized major features of bacterial and mammalian cell in context of antibacterial therapy. Much details were given to model membranes and their application in mechanistic studies. Current challenge in antibacterial therapy and perspective of membrane mimics in antibacterial drug discovery were also provided.